Modeling and Coordinated Control of Multi-energy Coupled System with PV-Hydrogen-Energy Storage. Issue 4 (February 2019) - Zhao, Jingtao; Wu, Peihua; Zhang, Xiaoyan; Li, Zhe
Abstract: Given that the important influence upon the power network of strong randomness and the intermittent features in PV power, this paper is to construct a multi-complementary system, which combines the PV module, electrolysis of water produce hydrogen module, hydrogen fuel cell module and lithium battery energy storage module, all coupling with DC-bus of 800V. It is to build a mathematical model of PV, electrolyzer, hydrogen fuel cell and lithium battery. In this case, it does research on photovoltaic, electrolysis of water producing hydrogen, hydrogen fuel cell power, lithium battery energy storage and other on-grid system and coordinated control strategy. This control strategy not only can make the hybrid system power output controllable, but also can dramatically improve the utilization rate of solar energy and hydrogen energy, which make the usage of clean energy efficient. What's more, this system can smooth the fluctuation of DC-bus's voltage and let it stabilize at 800V and smooth the power of on-grid network. Finally, the simulating result by means of PSCAD/EMTDC tests verifies the efficiency of this hybrid system's coordinated control strategy.